Who ensures that society has the professionals it needs? Differences in the policy directions of three European countries. Issue 2 (3rd July 2021) - Griffioen, Didi M. E.; Ashwin, Paul; Scholkmann, Antonia
ABSTRACT: In this article, we examine how policy documents from three European countries – the Netherlands, Germany and England – position a key outcome of higher education: the development of high-level professionals. Our findings show significant differences between the policies in the three countries in terms of in definitions of high-level professionals, the characterization of the education needed to produce high-level professionals, and the mechanisms identified as ensuring the production of high-level professionals. Our findings show that in order to develop a comparative understanding of higher education outcomes across the European Higher Education Area (EHEA), it is necessary to examine the strategic and visionary perspective of national policies in different EHEA countries. This is significant given that the EHEA's claim to ensure common outcomes across its higher education systems.